2005
DOI: 10.1590/s0073-47212005000300012
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade de peixes do reservatório da UHE Escola Engenharia Mackenzie (Capivara), Rio Paranapanema, bacia do alto rio Paraná, Brasil, e a importância dos grandes tributários na sua manutenção

Abstract: ABSTRACT. Fish diversity in the UHE Escola Engenharia Mackenzie (Capivara) reservoir, Paranapanema River, upper Rio Paraná basin, Brazil, and the importance of large tributaries in its maitenance. Fish samples were taken in four stretches along a gradient formed by the UHE Escola Engenharia Mackenzie (Capivara) reservoir. The diversity of species was analyzed by the constance, index of Shannon-Wiener and similarity of the composition among stretches through the Jaccard's coefficient. The reservoir presents a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 6 publications
5
24
2
8
Order By: Relevance
“…Previous studies have found higher fish diversity in the upstream reaches of reservoirs, where the water flow is faster, than in the lentic zone closer to the dam (HOFFMANN et al 2005, BRITTO & CARVALHO 2006, PETESSE et al 2007. By contrast, in this study the transition zone had the highest Shannon diversity and number of recorded species.…”
Section: Resultscontrasting
confidence: 73%
“…Previous studies have found higher fish diversity in the upstream reaches of reservoirs, where the water flow is faster, than in the lentic zone closer to the dam (HOFFMANN et al 2005, BRITTO & CARVALHO 2006, PETESSE et al 2007. By contrast, in this study the transition zone had the highest Shannon diversity and number of recorded species.…”
Section: Resultscontrasting
confidence: 73%
“…A good example of this is the coexistence between A. bimaculatus and A. fasciatus in the reservoir, both abundant during the dry seasons. The abundance and coexistence of these two species was also observed by Hoffmann et al (2005), Galetti Junior et al (1990), Agostinho et al (1997aAgostinho et al ( ,1997b, Schifino et al (2004) and Teixeira et al (2005).…”
Section: Diversity and Evenness Indicessupporting
confidence: 53%
“…Os exemplares de peixes utilizados neste estudo foram provenientes das coletas realizadas por (Hoffmann et al 2005), no período maio de 2001 e maio de 2002 e mais duas de caráter complementar, a primeira em dezembro de 2003 e a segunda entre junho e julho de 2004. As coletas foram realizadas com redes de espera (malhas 7, 10 e 11) dispostas perpendicularmente às margens da represa, além de tarrafas para coleta de espécies menores nas margens.…”
Section: Amostragens E Coleta De Dados Morfométricosunclassified
“…Recentemente, em quatro trechos diferentes do reservatório (Cinzas, Cruzália, Sertanópolis e Porecatu), foram registradas 62 espécies de peixes (Hoffmann et al 2005), sendo que o trecho de Porecatu, contendo 31 espécies, é o que melhor caracteriza, em termos gerais, o ambiente de reservatório, devido ao seu caráter semi-lótico. Segundo o exposto acima e de acordo com a teoria ecomorfológica, espera-se que a morfologia reflita adaptações dos peixes existentes no reservatório, com a estrutura da assembléia refletindo as interrelações ecomorfológicas interespecíficas.…”
Section: Introductionunclassified